Pengujian Maksimal Penggunaan Ulang Masker Kain dengan Berbagai Jenis Bahan Baku Masker: Maximum Testing of Cloth Mask Reuse with Different Types of Mask Materials - Eni Ayu Putri; Hajrah Hajrah; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Cloth masks are used as personal protective equipment from exposure to foreign particles in the air, the use of cloth masks while can reduce the number of medical mask waste number. Cloth masks in use need to be washed repeatedly, so it is necessary to know the effect of washing on the effectiveness and maximum duration of use. The purpose of this study was to determine the effectiveness of the use of cloth masks after going through a repeated washing process by looking at their characteristics and filtration ability in filtering bacteria. The experimental research method was carried out by making 3 types of cloth masks from different masks raw materials, cloth masks were washed 10, 20, 30, 40, and 50 times. Then it is characterized by looking at water absorption, steam filtration, translucency, and ability to filter Streptococcus aureus bacteria. The results showed that the average absorption capacity of the mask in the 10th wash was >60 seconds, while in the 50th washing it was <60 seconds. The results of the steam filtration test are only 4.5% of the masks that have changed characteristics. The results of the translucency test in the 10th wash were 7.4 ±1.67 lux while in the 50th washing the average was 11.4 ±1, 94 lux. The results of the bacterial mask filtering test in the 10th washing were 5.3±5.57 colonies, while in the 50th washing the average was 1.9±2.2 colonies. Based on the characteristic test and bacterial filtering test, there was no significant change in the three types of cloth masks in each wash so that the three types of cloth masks were still effective until the 50th washing. The conclusion is that the cloth masks made have the potential to be used by the public as an effort to prevent the transmission of infectious diseases.